2004
DOI: 10.1007/s11013-004-1065-7
|View full text |Cite
|
Sign up to set email alerts
|

Not Your ?Typical Island Woman?: Anorexia Nervosa is Reported Only in Subcultures in Cura�ao

Abstract: Anorexia nervosa (AN), once thought to be a problem of wealthier, Western countries has now been documented in survey studies and case reports across geographic and economic groups; however, few epidemiological studies including interview have been done on these populations. We report on a comprehensive study on Curaçao, a Caribbean island in economic transition, where the majority of the population is of predominantly black African origin. As part of an epidemiological study on the island of Curaçao indigenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 33 publications
3
29
0
Order By: Relevance
“…8 Our findings are consistent with the assumption that acculturation plays a role in the development of eating disorders and that women in ethnic minorities are at greater risk of developing eating disorders when they identify more with White, middle-class values. 1,7,9 This case report shows that, under the right circumstances, Black women who are vulnerable to AN do indeed develop the disorder. It illustrates that the internalization of the Western thinness ideal can play an important mediating role in diet restriction, leading eventually to AN.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…8 Our findings are consistent with the assumption that acculturation plays a role in the development of eating disorders and that women in ethnic minorities are at greater risk of developing eating disorders when they identify more with White, middle-class values. 1,7,9 This case report shows that, under the right circumstances, Black women who are vulnerable to AN do indeed develop the disorder. It illustrates that the internalization of the Western thinness ideal can play an important mediating role in diet restriction, leading eventually to AN.…”
Section: Resultsmentioning
confidence: 69%
“…They were of mixed race, were more highly educated, and had lived overseas, all of which made them quite different from the Black majority on the island. 7 The illness history of our case illustrates that her ethnic background did not protect her from developing AN. It highlights the contribution of sociocultural influences in the form of local norms regarding body size and shape to the development of AN.…”
Section: Resultsmentioning
confidence: 75%
“…This is consistent with research which has found that social comparison with white peers may promote body dissatisfaction amongst nonwestern schoolgirls 20 who may overcorrect 21 their body shape in order to be accepted by their western peers. Research 14,15 has also suggested that women may use the body as a vehicle for the expression of identity, particularly during times of rapid social change when they may need to redefine themselves. 16,22 Black, South African schoolgirls may thus be particularly at risk for the development of body dissatisfaction and dysfunctional eating attitudes and behaviors, during the period of ethno-cultural integration and rapid socio-cultural transition that is occurring in post-apartheid South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the Curacao study, the effect of migration is difficult to separate from race, socio-economic class and educational factors (Katzman et al, 2004). To explore these and other possibilities, we conducted an in-depth qualitative study of subjective accounts of such events among young Czech women with eating disorders.…”
Section: Introductionmentioning
confidence: 99%